Fish physiology - Hoar, W.S.; Randall,D.J. (New York, New York Academic Press, 1969)
v. 1. Excretion, ionic regulation, and metabolism -- v. 2. The endocrine system -- v. 3. Reproduction and growth, bioluminescence, pigments, and poisons -- v. 4. The nervous system, circulation, and respiration -- v. 5. Sensory systems and electric organs -- v. 6. Environmental relations and behavior
Keywords: Fishes--Physiology.